Effect of Platelet-Rich Plasma on Autologous Chondrocyte Implantation for Chondral Defects: Results Using an In Vivo Rabbit Model. Issue 3 (10th March 2022) - Kato, Yuki; Yanada, Shinobu; Morikawa, Hitoshi; Okada, Takuya; Watanabe, Masatoki; Takeuchi, Shunsuke
Background: Articular cartilage repair remains challenging despite the availability of techniques, including autologous chondrocyte implantation (ACI) for repairing large cartilage defects. Platelet-rich plasma (PRP) therapy, a novel therapy focused on chondrocyte regeneration, needs to be investigated regarding its potential to improve the outcomes of ACI. Purpose: To examine the effect of PRP therapy on the outcomes of cartilage repair using the ACI procedure in a rabbit model of knee joint cartilage damage. Study Design: Controlled laboratory study. Methods: A total of 30 knees in 15 Japanese White rabbits (joint cartilage damage model) were divided into nontreatment (n = 7), PRP (n = 8), ACI (n = 7), and combined ACI and PRP (n = 8) groups. At 4 weeks and 12 weeks postoperatively, histological and visual examination of the surgical site was performed, and the regenerated cartilage and calcified bone areas were measured by imaging the specimens. Results: Pretransplantation evaluation in the cultured cartilage showed the histological properties of hyaline cartilage. At 4 weeks postoperatively, the regenerated cartilage area at the surgical site showed a larger safranin O–positive area in the ACI group (2.73 ± 4.46 mm 2 ) than in the combined ACI and PRP group (1.71 ± 2.04 mm 2 ). Calcified bone formation in the ACI group was relatively lower than that in the other groups. Cartilage repair failure occurred in all groups at 12 weeks postoperatively. Conclusion: The authors found no positive effects of PRP on the outcomes of ACI in a rabbit model. There was a smaller safranin O–positive region with the addition of PRP to ACI compared with ACI alone. In the subchondral bone, bone formation might have been promoted by PRP. Clinical Relevance: Administering PRP at the time of ACI may not have a positive effect and may have deleterious effects on cartilage engraftment and regeneration.